2009
DOI: 10.1002/pro.32
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into the catalytic mechanism of gluconate 5‐dehydrogenase from Streptococcus suis: Crystal structures of the substrate‐free and quaternary complex enzymes

Abstract: Gluconate 5-dehydrogenase (Ga5DH) is an NADP(H)-dependent enzyme that catalyzes a reversible oxidoreduction reaction between D-gluconate and 5-keto-D-gluconate, thereby regulating the flux of this important carbon and energy source in bacteria. Despite the considerable amount of physiological and biochemical knowledge of Ga5DH, there is little physical or structural information available for this enzyme. To this end, we herein report the crystal structures of Ga5DH from pathogenic Streptococcus suis serotype 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…Although it is not uncommon for a functionally competent catalytic triad (SYK) to be intact in the structures of the apo forms of some proteins annotated as 3-ketoacyl-(acyl carrier protein) reductases (PDB accession numbers 2UVD [21], 3LYL, 3OSU, 4M8S, etc. ), as well as in the structures of the apo forms of other members of the short-chain dehydrogenase superfamily (PDB accession numbers 1K2W [53], 3CXR [54], 2EWM [55], etc. ), it is unexpected that the structures of the apo forms of vcFabG and ecFabG would exhibit different conformations.…”
Section: Nadph Binding In Wild-type Vcfabgmentioning
confidence: 99%
“…Although it is not uncommon for a functionally competent catalytic triad (SYK) to be intact in the structures of the apo forms of some proteins annotated as 3-ketoacyl-(acyl carrier protein) reductases (PDB accession numbers 2UVD [21], 3LYL, 3OSU, 4M8S, etc. ), as well as in the structures of the apo forms of other members of the short-chain dehydrogenase superfamily (PDB accession numbers 1K2W [53], 3CXR [54], 2EWM [55], etc. ), it is unexpected that the structures of the apo forms of vcFabG and ecFabG would exhibit different conformations.…”
Section: Nadph Binding In Wild-type Vcfabgmentioning
confidence: 99%
“…On the other hand, Ga5DH, which has a straight ␣-helix 4 and long ␣-helix 5, accepts the cofactor (51), although all of the above-mentioned SagDhuD residues, such as Pro 126 , Cys 149 , Gly 168 , Gly 169 , and Pro 193 , are completely conserved in Ga5DH. In this study, SagDhuD was experimentally demonstrated to exhibit an NADH-dependent reductase/dehydrogenase activity, suggesting that SagDhuD also adopts a Ga5DH-like structure through conformational changes caused by the substrate/ cofactor binding and that two structural conformations (i.e.…”
Section: Structural Comparison In the Sdr Familymentioning
confidence: 99%
“…The proteins are shown as PDB accession numbers: 1X1E, TT0495 protein from Thermus thermophilus HB8; 1PR9, human L-xylulose reductase; 6 3CXT, gluconate 5-dehydrogenase from Streptococcus suis type 2. 18 carbonyl oxygen atom at C2 of L-sorbose in the ternary His116Leu-SR-NADPH-L-sorbose complex structure (details are described in the text below). On the other hand, the side chains of Tyr157 and Lys161 form hydrogen bonds with the nicotinamide ribose of NADPH.…”
Section: The Active-site Structure Of Srmentioning
confidence: 99%